Hydrophilic Interaction Liquid Chromatography-Mass Spectrometry Characterization of Gangliosides in Biological Samples - Hájek, Roman; Jirásko, Robert; Lísa, Miroslav; Cífková, Eva; Holčapek, Michal (Analytical chemistry, 2017)
The hydrophilic interaction liquid chromatography (HILIC) coupled to a negative-ion electrospray ionization tandem mass spectrometry (ESI-MS/MS) method has been developed for the identification of a wide range of gangliosides in biological samples. Gangliosides consist of a backbone of sphingoid base and a polar oligosaccharide chain containing at least one sialic acid. Gangliosides are extracted by chloroform-methanol-water mixture, where an upper aqueous layer containing gangliosides and other polar lipid subclasses is further purified by C18 solid-phase extraction. The optimization of chromatographic conditions includes the column selection, mobile-phase composition, pH value, buffer type, and concentration with the goal to achieve the best chromatographic resolution and MS sensitivity. The identification of gangliosides and other polar lipids is based on accurate m/z values of [M-H]- ions and fragment ions as well measured by high-resolution MS. The detailed interpretation of MS/MS spectra enables the generalization of fragmentation pathways, which is then used for the differentiation of a, b, and c series of gangliosides. The structural assignment is further confirmed by agreement with the predicted retention behavior in HILIC mode on the basis of the correlation among the ganglioside retention, the number of saccharide units, and their sequence. The final HILIC/ESI-MS/MS method is applied for the analysis of porcine brain, human kidney, lungs, plasma, and erythrocytes resulting in unambiguous identification of 145 ganglioside species from 19 subclasses, which represents the highest number of reported gangliosides. Moreover, 71 sulfatides and 59 polar phospholipids (phosphatidylserines, phosphatidylinositols, lysophosphatidylinositols, and phosphatidylglycerols) are detected within a 15 min run.
Keywords: hydrofobní a hydrofilní interakce; Chromatography, High Pressure Liquid; mozek; Spectrometry, Mass, Electrospray Ionization; Gangliosides; vysokoúčinná kapalinová chromatografie; Swine; Hydrophobic and Hydrophilic Interactions; Brain; Erythrocytes; erytrocyty; zvířata; plíce; Humans; Tandem Mass Spectrometry; ledviny; prasata; tandemová hmotnostní spektrometrie; Kidney; hmotnostní spektrometrie s elektrosprejovou ionizací; gangliosidy; Lung; lidé; Animals